RANCANGAN BISNIS SABUN CUCI RAMAH LINGKUNGAN - Indah Setiawati; Bambang Soemanto; Yudi Syahrullah; Indah Widyarini (Universitas Galuh, 2022)
Waste cooking is a vegetable oil that can be processed into laundry soap products. Business opportunities based on waste cooking soap that are environmentally friendly need to be researched. This study aims to create an environmentally friendly laundry soap business design using the Business Model Canvas (BMC) method. Sources of data obtained from in-depth interviews with household scale soap producer Inti Herba. Based on the results of the analysis, there are 9 blocks used in designing an environmentally friendly laundry soap business based on waste cooking. Environmentally friendly products have a value proportion to green products which are products that are in demand by environmental activists/green consumers. Therefore, in this eco-friendly laundry soap business design, the market segment is housewives who are environmental activists. The other seven blocks studied using BMC show important aspects related to the design of an environmentally friendly laundry soap business from waste cooking.